2023
DOI: 10.3390/ma16216850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Early Strength Development of Concrete Mixed with Non-Sintered Hwangto Using Ultrasonic Pulse Velocity

Youngjin Nam,
Keesin Jeong,
Wonchang Kim
et al.

Abstract: Currently, in order to reduce the greenhouse gases of global warming, research on alternative cement materials is being actively conducted in the construction industry to reduce cement use, and it is judged to be important to evaluate the timing of form removal for the initial age. Therefore, in this study, we evaluated the initial mechanical properties of concrete in which cement was partially replaced with non-sintered hwangto (NHT). Specimens without NHT (namely, normal mortar (NM) and normal concrete (NC))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The early age model is used to evaluate the strength of concrete at an early age using UPV and to nondestructively gauge the time of vertical formwork demolding in the construction stage. To develop an early age model, researchers evaluated the compressive strength and UPV of concrete 24 h after concrete mixing and performed a regression analysis on the data, ultimately proposing a general exponential model [ 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early age model is used to evaluate the strength of concrete at an early age using UPV and to nondestructively gauge the time of vertical formwork demolding in the construction stage. To develop an early age model, researchers evaluated the compressive strength and UPV of concrete 24 h after concrete mixing and performed a regression analysis on the data, ultimately proposing a general exponential model [ 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies tested the statistical significance of the strength and UPV of heated and unheated concrete, and the results of the regression analysis were evaluated [ 21 ]. Concrete with a high-temperature history in the same UPV range showed a relatively high prediction rate in terms of compressive strength, and it was reported that crack formation owing to differences in the thermal expansion properties of mixed materials and voids owing to chemical decomposition contributed to the very low UPV [ 17 , 22 ]. Studies on the prediction of the strength of concrete at an early age using UPV have reported very low values, showing a different trend from the aforementioned research.…”
Section: Introductionmentioning
confidence: 99%
“…Among the non-destructive techniques employed for estimating compressive strength, the use of ultrasonic pulse velocity (UPV), which employs ultrasonic waves, has gained prominence. Consequently, numerous researchers are employing UPV to evaluate the mechanical properties or quality of concrete [ 20 , 21 , 22 ]. However, in the context of NSHC, additional research and analysis are required due to the lack of extensive experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changes in the chemical and mechanical properties of concrete exposed to high temperatures have continuously drawn attention.Recently, in response to global warming, various efforts have been made to reduce emissions from the cement manufacturing process, which involves high carbon dioxide emissions. Studies have been conducted on the utilization of industrial byproducts or solid waste as replacement materials for cement [4][5][6]. As for the replacement materials, several studies have investigated fly ash (FA), ground granulated blast furnace slag (GGBFS), and metakaolin (MK) as admixtures [7][8][9].…”
mentioning
confidence: 99%